Nurses' self‐efficacy and well‐being at work amid the COVID‐19 pandemic: A mixed‐methods study - Nahed Alquwez (Wiley, 2023)
Abstract Aims To explore the factors associated with the nurses' well‐being at work. Design A sequential explanatory mixed‐methods design. Methods The quantitative part of the study included a conveniently sampled 271 nurses employed in healthcare facilities in the Riyadh region of Saudi Arabia. A purposive sample of 21 nurses were interviewed in the qualitative part of the study. Data collection was performed from May to August 2021. This article followed the STROBE checklist. Results Nurses working in private hospitals reported higher level of self‐efficacy than nurses in public hospitals. Being a Filipino, working in private hospital, and having higher self‐efficacy were associated with better well‐being at work among nurses during the pandemic. The thematic analysis revealed four important themes in understanding their well‐being at work: safe work environment, ensuring staff nurses' health, leadership support, and solidarity in the workplace.